Engaging in writing to learn – Increasing the motivation during a long-term self-regulated learning training - Udvardi-Lakos, Nina; Endres, Tino; Glogger-Frey, Inga; Renkl, Alexander (Frontiers in Education, 2023)
University students should be able to self-regulate their learning to gain the most from their studies. Extended self-regulated-learning trainings can help students to reach that goal. A frequent problem of such trainings is that students’ motivation decreases over the course of training. To avoid this decrease, we combined a learning-journal-based, self-regulated-learning training with a learning environment teaching conditional knowledge about learning strategies, a guided peer-feedback system, and an optional intervention for students reporting low levels of motivation from the start of the semester. Four motivational variables were repeatedly measured over the course of ten weeks. Students (N = 103) in our training showed an increase in their self-efficacy and a decrease in cost associated with learning-journal-writing throughout the semester. The optional intervention led to an increase in the intrinsic value associated with the learning journals for students with low motivation. Our study suggests that this expanded self-regulated-learning training can help students maintain their motivation during a long-term training.